علاقة بعض مؤشرات المرفولوجية مع اداء بعض المهارات الحركية لممارسي رياضة الكاراتيه دو 15-16سنة - شريفي حمزة/كروش حاج بغداد (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
تهدف هذه الدراسة إلى الكشف عن طبيعة العلاقة الارتباطية بين بعض المؤشرات المورفولوجية (القياسات الجسمية)، مثل الطول، الوزن، وأطوال ومحيطات الأطراف، وأداء ثلاث مهارات حركية أساسية في رياضة الكاراتي-دو، وهي: زان كوتسوداشي (وضعية أمامية)، شوطو يوكي (ضربة جانبية باليد)، وجودان أجيوكي (صد علوي). وقد تم تنفيذ البحث على عينة مكونة من 30 لاعبًا من فئة الناشئين (15-16 سنة) ينتمون إلى نادي السلام ببلدية سيدي بوبكر - ولاية سعيدة، باستخدام المنهج الوصفي الارتباطي، حيث خضع المشاركون لقياسات جسمية دقيقة، وتم تقييم مهاراتهم الحركية من طرف لجنة تحكيم متخصصة. أظهرت نتائج التحليل الإحصائي أن هناك علاقات ارتباطية ذات دلالة إحصائية بين بعض المؤشرات المورفولوجية ومهارتي زان كوتسوداشي وشوطو يوكي، خاصة فيما يتعلق بالطول وطول الأطراف ومحيط الورك، بينما لم تظهر أية علاقة دالة مع مهارة جودان أجيوكي. وتدل هذه النتائج على أن بعض الخصائص الجسمانية قد تؤثر فعليًا في جودة الأداء المهاري، لا سيما في المهارات التي تتطلب التوازن والثبات أو السرعة والدقة. في المقابل، فإن المهارات ذات الطابع الدفاعي مثل جودان أجيوكي ترتبط بدرجة أكبر بالكفاءة العصبية العضلية أكثر من ارتباطها بالأبعاد الجسمانية. // // // // // // Abstract: This study aims to explore the correlational relationship between specific morphological indicators (body measurements)—such as height, weight, and the lengths and circumferences of limbs—and performance in three fundamental motor techniques in Karate-Do: Zenkutsu-dachi (front stance), Shuto-uke (knife-hand block), and Jodan-age-uke (high block). The research was conducted on a sample of 30 junior male athletes aged 15 to 16, affiliated with the El-Salam club in the municipality of Sidi Boubekeur, Saïda Province. A descriptive correlational approach was employed, involving detailed anthropometric assessments and technical performance evaluations conducted by a panel of expert judges. Statistical analysis revealed significant correlations between certain morphological indicators and performance in Zenkutsu-dachi and Shuto-uke, particularly regarding height, limb length, and hip circumference. In contrast, no significant correlation was observed for Jodan-age-uke. These findings suggest that specific body characteristics may influence the quality of motor execution, especially in techniques requiring balance, stability, speed, or precision. Conversely, defensive techniques such as Jodan-age-uke appear to be more strongly associated with neuromuscular coordination than with morphological traits.
LES-2025-25
Keywords: الكراتي دو; المؤشرات المورفولوجية; لمهارات الحركية; 15-16سنة